Trap-Neuter-Return Activities in Urban Stray Cat Colonies in Australia - Tan, Kuan (Animals (Basel), 2017)
SIMPLE SUMMARY: Urban stray cats in Australia are poorly regarded because of wildlife predation and nuisance behaviors. However, current methods of population control via low level culling are ineffective. Effective control requires culling 30% to 50% of the population every six months, which is prohibitive for municipalities. Overseas, trap, neuter and return is frequently used to control urban cat numbers, and reduce nuisance behaviors, but is considered illegal in many Australian jurisdictions. An anonymous questionnaire was used to gather data on trap, neuter and return of urban stray cats in Australia. Respondents were mostly middle-aged women, and more participated as individuals than with organizations. Colony size decreased from a median of 11.5 cats to 6.5 cats over 2.2 years, through adoptions and desexing a median of 69% of the colony. Cats were fed once or twice daily, and provided with prophylactic health care. Programs were largely funded by private sources, with some funding by animal welfare organizations. We conclude that trap, neuter and return associated with high desexing rates in colonies, and adoption of kittens and friendly adults substantially reduces colony size, and improves the welfare of cats and kittens. This model is cost-effective for municipalities, and should be legalized in Australia. ABSTRACT: Trap, neuter and return (TNR) describes a non-lethal approach to the control of urban stray cat populations. Currently, in Australia, lethal control is common, with over 85% of cats entering some municipal pounds euthanized. No research has been published describing TNR activities in Australia. Adults involved with TNR in Australia were invited to participate. Data from 53 respondents were collected via an anonymous online questionnaire. Most respondents were females 36 to 65 years of age, and slightly more participated in TNR as individuals than as part of an organization. Respondents generally self-funded at least some of their TNR activities. The median number of colonies per respondent was 1.5 (range 1 to over 100). Median colony size declined from 11.5 to 6.5 cats under TNR over a median of 2.2 years, and the median percent reduction was 31%; this was achieved by rehoming cats and kittens and reducing reproduction. A median of 69% of cats in each colony were desexed at the time of reporting. Most respondents fed cats once or twice daily, and at least 28% of respondents microchipped cats. Prophylactic healthcare was provided to adult cats and kittens, commonly for intestinal parasites (at least 49%), and fleas (at least 46%); vaccinations were less common. Time-consuming activities for respondents were feeding (median 4 h/week) and locating resources (median 1.1 h/week). These findings indicate that TNR, when involving high desexing rates within colonies, adoption of kittens and friendly adults, and ongoing oversight by volunteer caretakers, can reduce cat numbers over time, improve health and welfare of cats and kittens, and is largely funded by private individuals and organizations.